Comparative Study of Photoswitchable Zinc‐Finger Domain and AT‐Hook Motif for Light‐Controlled Peptide–DNA Binding. Issue 19 (4th March 2019) - Murawska, Gosia M.; Poloni, Claudia; Simeth, Nadja A.; Szymanski, Wiktor; Feringa, Ben L.
Abstract: DNA–peptide interactions are involved in key life processes, including DNA recognition, replication, transcription, repair, organization, and modification. Development of tools that can influence DNA–peptide binding non‐invasively with high spatiotemporal precision could aid in determining its role in cells and tissues. Here, the design, synthesis, and study of photocontrolled tools for sequence‐specific small peptide‐DNA major and minor groove interactions are reported, shedding light on DNA binding by transcriptionally active peptides. In particular, photoswitchable moieties were implemented in the peptide backbone or turn region. In each case, DNA binding was affected by photochemical isomerization, as determined in fluorescent displacement assays on model DNA strands, which provides promising tools for DNA modulation. Abstract : Controlling DNA binding : Sequence‐specific small peptide–DNA major and minor groove interactions can be controlled by irradiation. Specifically, photoswitchable azobenzene moieties were implemented in the peptide backbone or turn region of transcriptionally active peptides. DNA binding affinity was affected by photochemical isomerization, which provides promising tools for DNA modulation.